Roles of positive psychological outcomes in future health perception and mental health problems: A report from the Childhood Cancer Survivor Study. Issue 12 (27th September 2018) - Weinstein, Aurélie G.; Henrich, Christopher C.; Armstrong, Gregory T.; Stratton, Kayla L.; King, Tricia Z.; Leisenring, Wendy M.; Krull, Kevin R.
Abstract: Objective: Positive psychological outcomes among adolescent and young adult survivors of childhood cancer may influence long‐term health status. We examined posttraumatic growth (PTG) and Life satisfaction (LS) in adolescence, and their impact on future emotional and physical health status in young adulthood. Methods: Survivors (n = 2802) from the Childhood Cancer Survivor Study were longitudinally analyzed across social, emotional, and physical factors during adolescence (12–17 years old), and PTG (PTG‐Inventory) and LS (Cantril‐Ladder‐of‐Life) during young adulthood (19–24 years old). The impact of PTG and LS on survivors' future long‐term mental health, physical health, and social skills was also examined (23–28 years old) using Structural Equation Modeling. Results: Survivors reported high levels of LS (M = 7.43, range 1 to 10) and a positive impact from their cancer experience (M = 48.78, range 0 to 105). Adolescent predictors of higher PTG included older age at diagnosis ( p  = 0.001), experiencing more severe chronic health conditions ( p  = 0.01), cancer recurrence/relapse ( p  = 0.01), and being diagnosed with a non‐CNS cancer ( p  = 0.001). Higher perceived general health ( p  = 0.01), higher social skills ( p  = 0.001), and diagnosis with a non‐CNS cancer ( p  = 0.02) were associated with higher LS. Higher PTG during young adulthood predicted poorer perceived health ( p  = 0.04) and worse emotional health ( p  = 0.001) in later adulthood. Higher LS predicted better emotional health ( p  = 0.001) and better perceived health ( p  = 0.001). Conclusions: While LS was found to help survivors have better perceived long‐term emotional and physical health outcomes, survivors with higher PTG fond both positive and negative impacts from cancer. Future therapeutic trials to improve LS should be considered.